Pola Komunikasi Kehidupan Sosial Keagamaan Kawasan Kumuh Kampung Pemulung Kota Bandar Lampung - Fitri Yanti (Communicatus: Jurnal Ilmu komunikasi, 2019)
This study aims to analyze the communication patterns of religious social life in the slum areas of scavenger villages in the city of Bandar Lampung. This study uses a qualitative approach that is oriented towards the explanation of natural descriptive data by taking 11 informants as scavenger families. What is the social and social life of the scavengers who are not recognized because of their shortcomings and status that are not the same as the surrounding elite and middle society. The results showed that, the slum dwellers in the village were basically not only "coexistence" but also "cooperation". The communication pattern of the social and religious life of the slum areas of the Pemulung village in terms of religious life gave birth to conditions and habits from the start of their religious activities, understanding and behavior. This can be seen from the habit when they worship. While from the social life patterns born individual patterns and group patterns to join or not with the surrounding community. Penelitian ini bertujuan menganalisis pola komunikasi kehidupan sosial keagamaan kawasan kumuh kampung pemulung di kota Bandar Lampung. Penelitian ini menggunakan pendekatan kualitatif yaitu berorientasi pada penjelasan data deskriptif yang alamiah dengan mengambil informan 11 kepala keluarga pemulung. Bagaimana kehidupan sosial kemasyarakatan dan keagamaan masyarakat pemulung yang tidak diakui karena kekurangan dan status mereka yang tidak sama dengan masyarakat elit dan menengah di sekitarnya. Hasil penelitian menunjukkan bahwa, masyarakat kumuh kampung pemulung pada dasarnya tidak hanya “koeksistensi” melainkan juga “kooperasi”. Pola komunikasi kehidupan sosial dan keagamaan kawasan kumuh kampung Pemulung dari segi kehidupan beragama melahirkan kondisi dan kebiasaan dari mulai aktivitas, pemahaman, dan prilaku agama mereka.  Hal ini terlihat dari kebiasaan kapan mereka beribadah. Sedangkan dari pola kehidupan sosial lahir pola individu dan pola berkelompok untuk bergabung atau tidak dengan masyarakat sekitar.